2019
DOI: 10.1055/s-0038-1676095
|View full text |Cite
|
Sign up to set email alerts
|

What is the Impact of Positive Airway Pressure in Nasal Polyposis? An Experimental Study

Abstract: Introduction It has been hypothesized that increasing the interstitial hydrostatic pressure within the sinonasal mucosa of patients with nasal polyposis (NP) might decrease the size of nasal polyps. Objective To evaluate the effects of positive airway pressure, delivered by a continuous positive airway pressure (CPAP) device, in patients with NP and in control subjects. Methods Twelve patients with NP and 27 healthy subjects were exposed to CPAP (20 cm H2O) for 2 hours. Visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…All patients gave their written and informed consent to participate in the study. Given the exploratory nature of the study and scarce information in the literature, a convenience sample size was decided based on examples of published studies 32,33 . The study was developed in the context of a PhD project and funded by a prize from the NOVARTIS|Excellence in Medicine program and a grant from NOVA Saúde (Universidade Nova de Lisboa Rectorate).…”
Section: Methodsmentioning
confidence: 99%
“…All patients gave their written and informed consent to participate in the study. Given the exploratory nature of the study and scarce information in the literature, a convenience sample size was decided based on examples of published studies 32,33 . The study was developed in the context of a PhD project and funded by a prize from the NOVARTIS|Excellence in Medicine program and a grant from NOVA Saúde (Universidade Nova de Lisboa Rectorate).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the accuracy of the pressure-response imbalance theory of the pathogenesis of NP, in one study, patients with NP were acutely exposed to continuous positive pressure in the nasal cavity. Surprisingly, the nasal polyp volume was reduced 40 , probably due to the successful transmission of continuous pressure to the affected tissue, raising the interstitial hydrostatic pressure and consequently facilitating the flow of water back into the capillaries.…”
Section: Pressure Imbalance In Nasal Polyposismentioning
confidence: 99%
“…6 However, new therapeutic modalities that act directly on mechanical dysfunction have been suggested, mainly trying to increase interstitial hydrostatic pressure. 12,13 By the way, studies reported that the presence of mesenchymal stem cells in the polypoid tissue was associated with a decreased number of inflammatory cells and proinflammatory interleukins, as well as increased regulatory T-cells and interleukin-10 (IL-10), which consequently led to the reduction of the chronic inflammatory process. 14,15 In addition, it was demonstrated that nasal polyp-derived mesenchymal stem cells presented decreased expression of immunoassociated molecules, but presented overexpression of progenitor genes when compared with bone marrowderived mesenchymal stem cells, 16 which may be associated with the altered remodeling process.…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, new therapeutic modalities that act directly on mechanical dysfunction have been suggested, mainly trying to increase interstitial hydrostatic pressure. 12 13 …”
Section: Introductionmentioning
confidence: 99%